The Role of Artificial Intelligence in Digital Marketing Innovation - Ikhwan Taufik; Andriyatna Agung Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this article is to describe and analyze the basic concepts of Artificial Intelligence (AI) and identify fields of AI derivatives that can be applied in digital marketing innovations. This article also explores the various applications of AI, and their impact on the effectiveness and efficiency of digital marketing. AI plays a significant role in digital marketing. AI has changed the way companies interact with customers and how they manage advertising. By combining machine intelligence and data analysis, companies can improve the targeting, personalization, and effectiveness of their ads, resulting in a better experience for customers and better results for the business they run. The recommendation is for the machine learning sub-field to continue to be developed to get more benefits. However, other sub-fields in AI are equally important to develop.